STUDI EKSPERIMENTAL PENDINGIN PASIF LAMPU LIGHT EMITTING DIODE UNTUK APLIKASI PADA PENERANGAN RUANGAN - Hidayat, Rahmat; Eka Pramono, Gatot; ., Nurrohman (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2017)
In the present day, light emitting diode (LED) is used for domestic purposes up to the industry, such as for lighting room. Although relatively expensive, LED are highly in demand by the public because it produces a brighter light and uses very low power so it can save electrical energy. LED produces heat emanating from the chip. Generation of heat will result in the degradation of performance of the LED. To keep the performance of the LED light remains good, a process is needed for the LED to have a better heat dissipation. It is achieved by using heatsink as an element to release heat. This research is a fundamental research which aims to determine heat transfer characteristics on LED of Chip on Board (COB) type. From the experimental results, it is obtained that the greater the value of the input voltage, the higher the value of lux but the performance of the LED decreases with higher junction temperature value. The performance and light produced by the LED are highly dependent on the type of heatsink materials. When aluminum used the value of lux obtained was 1363 lm/m2 while for aluminum-copper combination the value of lux obtained was 1251 lm/m2. The value of heatsink area greatly affected the temperature of the thermal pad.